FINANCIAL DETERMINANTS OF MUDHARABAH AND MUSYARAKAH FINANCING: EMPIRICAL INSIGHTS FROM INDONESIAN ISLAMIC COMMERCIAL BANKS - Dinda Ruliana Dewi; Khusnudin (I-Finance Journal, 2024)
This study aims to analyze the relationship between mudharabah and musharakah financing in Islamic Commercial Banks with six independent variables: Return on Assets (ROA), Return on Equity (ROE), Financing to Deposit Ratio (FDR), Operating Costs to Operating Income (BOPO), and Non-Performing Financing (NPF). The population of the study was Islamic Commercial Banks registered with the Financial Services Authority (OJK), with financial data samples from seven banks during the period 2018–2023.This study uses a quantitative approach with panel data regression analysis. The results of the study indicate that BOPO has a significant positive impact on mudharabah and musharakah financing, while ROA, CAR, and NPF have a significant negative impact. Conversely, ROE and FDR do not have a significant effect on the financing. Overall, the independent variables in this study explain 56.72% of the variation in mudharabah and musharakah financing, while the rest is influenced by other factors outside this research model.The conclusion of this study emphasizes the importance of managing financial performance indicators such as ROA, CAR, BOPO, and NPF to optimize mudharabah and musharakah financing.